Pelaksanaan Perjanjian Jual Beli Tenaga Listrik Antara PT. PLN (Persero) dengan Pelanggan Rumah Tangga di Kecamatan Pangkalan Kerinci Kabupaten Pelawawan - Regina, Shilvia; Abdillah, Satrio (Fakultas Syariah INSURI Ponorogo, 2023)
The need for electrical energy is the lifeblood of human life; in that case, if you want electricity, you must use the services of PT. PLN (Persero) with the terms and conditions of the agreement between the customer and PT. PLN (Persero). Public relations, both people and PT. PLNs, which are in a position called customers, were born on a bond of agreement. However, several problems occurred between the customer and PT. PLN regarding the agreement that needed to be carried out correctly. The formulation of the problem in this study is how the implementation of the power purchase agreement between PT. PLN (Persero) with household customers in Pangkalan Kerinci District, Pelalawan Regency, and what factors cause obstacles in the power purchase agreement in Pangkalan Kerinci District, Pelalawan Regency. The research method is a sociological, legal research method, namely legal research that wants to see the correlation of people's opinions as customers of PT. PLN (Persero) related to the electricity purchase agreement letter between the community as customers of household needs. The study results show that implementing these rights and obligations and the things agreed upon by the parties in a large percentage can be carried out. And the inhibiting factors are delays in electricity payments with complete or temporary disconnections, pole planting, and parallel connections.